Examination of corrosion under insulation using gamma ray computed tomography. Issue 1 (April 2020) - Sipaun, S; Ab Rahman, M F; Hasan, H; Shari, M R; Mahmood, A; Abdullah, N; Mustapha, M
Abstract: In this paper, we propose a screening and scanning approach using gamma ray transmission measurements and computed tomography (CT) to detect and locate corrosion areas in a pipeline. Screening obtains interval measurements of collimated gamma ray along the length of pipe, while scanning gives cross sectional images at the investigated area. The CT scanner consists of a clamped on mechanical gantry, a 1" × 1" NaI(Tl) scintillation detector, 11mCi Ba-133 source, 15mm x 5mm lead collimators and Ludlum scaler ratemeter. This technique was shown to be an effective way to determine the wall loss and erosion areas of at 2.5mm thickness. Several locations of an insulated pipe were screened and scanned. Using a portable gamma ray CT scanner we present the results, where the cross sectional image can indicate the occurrence of corrosion under insulator.